2021
DOI: 10.3389/fcimb.2021.658070
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of a Stable and Transferable blaNDM-5-Positive Plasmid With Low Fitness Cost Leading to Ceftazidime/Avibactam Resistance in KPC-2-Producing Klebsiella pneumoniae During Treatment

Abstract: The emergence and prevalence of carbapenem-resistant Enterobacteriaceae (CRE) have drawn worldwide attention. Ceftazidime/avibactam (CAZ/AVI) gives us a valuable alternative strategy to treat CRE infections. Unfortunately, CAZ/AVI resistance could occur during CAZ/AVI treatment. The CAZ/AVI-resistant Carbapenem-resistant Klebsiella pneumoniae (CR-KP) (KP137060) and earlier CAZ/AVI-susceptible isolate (KP135194) from the same hospitalized patient were collected at Fujian Medical University Union Hospital betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 49 publications
3
8
0
Order By: Relevance
“…In addition, the detection rate of bla NDM in children was significantly higher than that in adults. Our results are similar to those of a previous study indicating that acquiring a bla NDM-5 -harboring plasmid led to resistance to CAZ-AVI in KPC-2-producing K. pneumoniae during treatment ( Huang et al., 2021 ). With the CAZ-AVI combination, AVI protects CAZ from degradation by various serine beta-lactamases, thus promoting CAZ-AVI activity.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the detection rate of bla NDM in children was significantly higher than that in adults. Our results are similar to those of a previous study indicating that acquiring a bla NDM-5 -harboring plasmid led to resistance to CAZ-AVI in KPC-2-producing K. pneumoniae during treatment ( Huang et al., 2021 ). With the CAZ-AVI combination, AVI protects CAZ from degradation by various serine beta-lactamases, thus promoting CAZ-AVI activity.…”
Section: Discussionsupporting
confidence: 91%
“…We also found eight isolates that encoded two carbapenemases, either IMP-4 and NDM-1 or KPC-2 and NDM-5. Several studies have revealed that the convergence of bla KPC-2 and bla NDM-5 or the coexistence of bla IMP-4 and bla NDM-1 in a single strain has the ability to extend the resistance profile of the bacteria, allowing the bacteria to potentially be transmitted between patients ( 31 33 ), posing a significant threat to public health. Therefore, it is necessary to strengthen the surveillance of these isolates among children to improve clinical treatment and management.…”
Section: Discussionmentioning
confidence: 99%
“…However, many studies have shown that some plasmids can persist in bacterial populations for a long time, even without positive selection, which is referred to as the "plasmid paradox" (Harrison and Brockhurst, 2012). For example, it is reported that the acquisition of mobile bla NDM-5positive plasmids in Enterobacteriaceae or K. pneumoniae showed little fitness cost on host bacteria (Ma et al, 2020;Huang et al, 2021). It is plausible that antibiotic resistance is determined by interactions between the resistance gene and bacterial host, not only by the existence of the resistance gene (Praski Alzrigat et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…These two drugs have been identified by the World Health Organization as the last lines of defense against infections caused by MDR Gramnegative bacteria (He et al, 2019). With the dissemination of carbapenem resistance gene bla NDM and polymyxin resistance gene mcr, tigecycline has been the final choice in the treatment of MDR infections (Choi et al, 2020;Huang et al, 2021). However, novel plasmid-mediated tigecycline resistance genes tet(X3/X4) in bacteria of human and animal origin were identified in 2019 in China.…”
Section: Introductionmentioning
confidence: 99%